ASSESSMENT OF THE INFLUENCE OF PRODUCTION AND TECHNOLOGICAL AND OPERATING FACTORS ON THE EMISSION CHARACTERISTICS OF GAS TURBINE ENGINES - Якушенко, О. С.; Чумак, О. І.; Охмакевич, В. М.; Мільцов, В. Є. (Proceedings of National Aviation University (archive), 2021)
Methods for obtaining emission characteristics of aircraft gas turbine engines are considered. The method of conducting a numerical experiment aimed at obtaining the emission characteristics of gas turbine engines, which is based on a mathematical model of the engine process. The technique allows to take into account the influence of production-technological and operational factors on the emission characteristics of the engine. The emission characteristics of the PS-90A engine obtained as a result of the experiment are given.